2019
DOI: 10.1038/s41598-019-43057-1
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of Trichinella spiralis-activated macrophages can ameliorate both Th1- and Th2-activated inflammation in murine models

Abstract: Trichinella spiralis is a zoonotic nematode and food borne parasite and infection with T . spiralis leads to suppression of the host immune response and other immunopathologies. Alternative activated macrophages (M2) as well as T reg cells, a target for immunomodulation by the helminth parasite, play a critical role in initiating and modulating the host immune response to parasite. The precise mechanism by which helminths modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 98 publications
(84 reference statements)
6
42
0
Order By: Relevance
“…Trichinella sp infection or their products protect experimental hosts from several immune diseases 25 such as type 1 diabetes (T1D) in NOD mice, 26 inflammatory bowel diseases (IBD), [27][28][29][30][31][32][33][34] experimental autoimmune encephalomyelitis (EAE) 35,36 and adjuvant arthritis. 37 Regarding other helminths, Th2 signals were reported to be essential for the anti-arthritic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Trichinella sp infection or their products protect experimental hosts from several immune diseases 25 such as type 1 diabetes (T1D) in NOD mice, 26 inflammatory bowel diseases (IBD), [27][28][29][30][31][32][33][34] experimental autoimmune encephalomyelitis (EAE) 35,36 and adjuvant arthritis. 37 Regarding other helminths, Th2 signals were reported to be essential for the anti-arthritic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Trichinella spiralis infection inhibits epithelial and crypt cell destruction and sustains mast cell stabilization, which prevents mucosal mast cell hyperplasia and exacerbates motor responses against intestinal inflammation (Serna et al, 2006). ES products from adult T. spiralis (AES) alleviate IBD with acute inflammatory colonic disease in mice induced by dextran sodium sulphate, which was mediated by inhibition of Th1/Th17 proinflammatory cytokines and an increase in the production of anti-inflammatory Th2/Treg regulatory cytokines in the lymphocytes of colon, mesenteric lymph node and spleen of mice treated with AES (Yang et al, 2014;Kang et al, 2019). Motomura et al (2009) showed Fig.…”
Section: Application Of T Spiralis or Its Products To Modulate Ibdmentioning
confidence: 99%
“…Molecules released by T. spiralis Trichinella spiralis can survive for long periods in the host, and this is mediated by the parasite's ability to modulate the host immune response through the secretion of immunomodulatory molecules (Yang et al, 2013;Liu et al, 2014;Sun et al, 2015;Tang et al, 2015;Cvetkovic et al, 2016;Guo et al, 2016) (table 2). ES products released by the different life stages of T. spiralis are involved in acute inflammatory responses and modulate molecular cross-talk between the parasite and host (Sun et al, 2011;Kang et al, 2019).…”
Section: Application Of T Spiralis or Its Products In Therapy Of Tummentioning
confidence: 99%
“…Treatment of J774A.1 or RAW264.7 macrophage cell lines with TsES significantly reduced the expression of LPS-induced pro-inflammatory cytokines, TNF-α, IL-1ÎČ, IL-6, and IL-12 but increased the expression of regulatory cytokine; this effect was observed even in the presence of ES products alone [5,6]. Adoptive transfer of macrophages obtained from T. spiralis-infected mice or TsES-treated macrophages into colitis or airway hyperresponsiveness (AHR) mouse models could ameliorate disease severity [7]. Although there have been several studies demonstrating TsES immunomodulatory capacity, few have focused on the characterization of effective molecules, and many of these molecules need to be further identified.…”
Section: Introductionmentioning
confidence: 98%